Adoption of chemical weed control technology among cassava farmers in south eastern Nigeria - Udensi, U.E.; Tarawali, G.; Ilona, Paul; Okoye, B.C.; Dixon, A. (2012)
Various factors influencing the adoption of weed control technologies in Abia State were studied. A multi-stage random sampling procedure was used to select 510 cassava farmers in 2006. Results showed that 56.5% of the respondents were females, that are largely (90.2%) in their productive years. Most (78.8%) of the total respondents were married, 83.3% attended formal schooling, 74.9% had households of more than 5 persons. All the respondents were basically smallholder farmers; with 46.9% were full time farmers. Fifty percent of the respondents had secure tenurial arrangements; 92.9% had more than 6 years of farming experience. Probit analysis shows that factors related to the adoption of weed control technologies were gender at 5% in the negative direction in Abia North (Zone 1) and 10% in the positive direction in Abia Central (Zone 2); age at 5% negatively in Zone 1, educational status at 5% in the positive direction in Zone 1 and 10% pooled (entire State), house-hold size at 5% and 1% positively in Zone 2 and the entire State, respectively. The coefficient for yield was positive and highly significant in Zone 1 and the entire State, the tenurial system was negative and significant at 5% level in Zone 2, as well as application problems but at 5% in Zone 1 and 10% pooled. Training on weed control and average income was positive and significant at 1% as well as farming experience at 5%. The coefficient for no definite market was negative and significant at 5% in Zone 1. The coefficient for the high cost of chemicals had a negative relationship with the adoption of chemical weed control technologies and was significant at the 1% level in Zone 2 and the entire State. The probit model for Abia South (Zone 3) could not be estimated because the percentages responding at all doses were the same. Hence policies should be adopted aimed at improving the educational levels of the farmers and encouraging the experienced farmers to increase adoption would be necessary; there is a need for the intensification of training and educational programs for the potential adopters of the weed control practices; programs that target both gender groups to ensure the equitable adoption of chemical control practices between males and females. Policies need to be designed to convert tenurial arrangements to more secure forms to increase the rate of adoption of weed control technology by the creation of markets for cassava, and the provision and subsidization of chemicals for weed control.